Analysis of treatment methods for canine and feline dermatomycosis - Liu, Luyan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Dermatomycosis is a kind of superficial infectious disease of skin, mucous membrane and skin accessory organ, which is caused by fungi. Dermatomycosis is a zoonosis characterized by recurrent, infectious and high morbidity. Nowadays, all studies on the treatment of dermatomycosis in cats and dogs are relatively scattered, so the purpose of this research is to analyze the therapeutic drugs of the dermatomycosis comprehensively by comparing the experimental data and results in other literatures, and point out the cons and pros and the target groups. Terbinafine is a good choice for both topical and systemic use or even as a medicated bath. For topical antibacterial treatment, ketoconazole, which has uncertain hepatotoxicity, is not recommended for young pets or those whose liver function is impaired. For systemic treatment, the itraconazole suspension is a better option, and fluconazole is not recommended to be the first choice if the sick animal is canine due to dogs’ poor sensitivity to it. Among the Chinese medicines, simple Chinese gallnut solution, compound prescription composed of Chinese gallnut, smoked plum and other 8 Chinese herbs, and a shampoo called Sanzi Qingbai are both safe and effective treatments, which is less likely to develop drug resistance. People should consider the overall condition of the sick animal and the nature of the drugs when choosing the most suitable treatment, and the combination of Chinese and Western medical treatments is also a new direction.